2021
DOI: 10.1111/ped.14514
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in short‐statured children born small for gestational age and treated with growth hormone

Abstract: Background Children born small for gestational age (SGA), particularly when associated with an extremely low birthweight (ELBW), have a higher risk of renal dysfunction. Growth hormone (GH) treatment is used to treat short‐statured children born SGA; however, its effects on renal function remain elusive, especially in those born SGA with ELBW. Methods Short‐statured children born SGA (N = 42) were included. Subjects were subdivided into two groups based on their birthweight: the ELBW group (N = 15) with a birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Therefore, concerns have been raised regarding the potential risk of GH treatment-associated catch-up growth to impair renal function in these children. Accordingly, we previously investigated the effect of GH treatment on renal function in short-statured children born SGA (n = 42) and found that 5-yr GH treatment did not decrease estimated glomerular filtration rate (eGFR) during the prepubertal period ( 14 ). In addition, the cumulative GH dosage was not correlated with changes in eGFR, indicating that GH treatment is unlikely to decrease eGFR during the prepubertal period in short-statured children born SGA ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, concerns have been raised regarding the potential risk of GH treatment-associated catch-up growth to impair renal function in these children. Accordingly, we previously investigated the effect of GH treatment on renal function in short-statured children born SGA (n = 42) and found that 5-yr GH treatment did not decrease estimated glomerular filtration rate (eGFR) during the prepubertal period ( 14 ). In addition, the cumulative GH dosage was not correlated with changes in eGFR, indicating that GH treatment is unlikely to decrease eGFR during the prepubertal period in short-statured children born SGA ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we previously investigated the effect of GH treatment on renal function in short-statured children born SGA (n = 42) and found that 5-yr GH treatment did not decrease estimated glomerular filtration rate (eGFR) during the prepubertal period ( 14 ). In addition, the cumulative GH dosage was not correlated with changes in eGFR, indicating that GH treatment is unlikely to decrease eGFR during the prepubertal period in short-statured children born SGA ( 14 ). However, there is a significant limitation in the previous study, as we did not investigate the effect of GH treatment on renal function during puberty despite the accumulating evidence that reductions in eGFR occur during puberty in those born SGA and/or with LBW ( 15 , 16 , 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%